Очищення полідисперсних шламів - Шестопалов, Олексій Валерійович; Шкоп, Андрій Олександрович (Національний університет "Львівська політехніка", 2016)
The features of process of flocculation of wastwater are considered. It was exposed, that efficiency of cleaning of wastwater depends on the particle-size of hard phase in water, initial concentration terms of leadthrough of flocculation. Will allow to intensify the exposure of conformities to the law of flocculat of wastwater cleaning process.
Keywords: полідисперсні шлами; полидисперсні шламові води; флокуляція; закономерності; смешение шлама с флокулянтом; водоочистка; полидисперсные шламовые воды